SUSTAINABLE DEVELOPMENT IN CHHATTISGARH STATE (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
Sustainable development goals (SDGs) are adopted by 193 members states including India at the United Nations (UN) summit in September 2015 are collection of 17 global goals aimed at improving the planet and the equality of human life around the world by the year 2030. Chhattisgarh has adopted 106 targets and 275 indicators at state level and 45 targets and 82 indicators for districts. This research paper focus on the need for sustainable development goals, progress that Chhattisgarh has achieved in meeting sustainable development goals as well as the district wise SDGs score.